Henry Brown Dillard papers - Dillard, Henry Brown
Miscellaneous papers of Lieutenant H. B. Dillard, platoon commander, 105th Combat Engineers, 30th Division, U.S. Army, with the II British Army in Flanders and the IV British Army in France during the battles of Ypres (Ieper) and the Somme. Includes correspondence, certificates, special and general orders, rosters, field messages, citations, poems, extracts from the letters of soldiers, photographs, and clippings.
Army officer.
Collection material in English.
Keywords: World War, 1914-1918 -- Campaigns -- Belgium; World War, 1914-1918 -- Campaigns -- Flanders; World War, 1914-1918 -- Campaigns -- France; Ieper (Belgium) -- History; Somme (France) -- History; Army officers